SYSTEM OF MEASURES TO INCREASE THE LEVEL OF CORPORATE SOCIAL RESPONSIBILITY AND COMPETITIVENESS OF THE ENTERPRISE ON THE INTERNATIONAL MARKET - Ткач, Вікторія; Пічугіна, Марина (Modern engineering and innovative technologies, 2022)
The paper considers corporate social responsibility as a significant competitive advantage of each economically stable enterprise, which manifests itself in the active public position and close interaction with the environment in which the company operate